Progress, Challenges, and Opportunities in Oxide Semiconductor Devices A Key Building Block for Applications Ranging from Display Backplanes to 3D Integrated Semiconductor Chips - Kim, Taikyu (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.